Concern for Rights and Identity in Nepal: A Rhetorical Analysis of Nepali Indigenous Leaders’ Speeches - Tamang, Hira Man (Journal of Indigenous Knowledge and Practice, 2025)
Rhetoric has the power to unite, divide, and liberate the people. However, Nepali indigenous leaders and activists often lack the skills to effectively use rhetorical language, despite possessing some competencies in rhetoric. This article aims to present some rhetorical ideas and skills to indigenous leaders and activists, enabling the indigenous people to benefit. To illustrate the point, this paper analyses the rhetoric of four indigenous activists who advocate for the rights and identity of indigenous people in Nepal. The speeches of Kiwahang Limbu, Dawa Tamang, Pasang Sherpa, and Rajesh Chaudhary have been used as the primary data for analysis. These speeches have been analysed based on Aristotle’s concept of Logos, Ethos, and Pathos, Toulmin’s model of Argument Claim, Ground, Warrant, Backing, Modifiers, and Rebuttal, and Fairclough’s Three-Dimensional Model of CDA. The study found that the Indigenous people could receive limited rights and experience their identity because of their leaders’ limited understanding and skills in rhetoric.